Mathematics
LoraleeLiukko933
43

Solve for the equation: 4(x+1)-3(2x+6)=-11

+4
(1) Answers
brainygirl7748

simplify the equation to the form, which is simple to understand 4(x+1)-3(2x+6)=-11 Reorder the terms in parentheses +(+4x+4)-3*(2x+6)=-11 Remove unnecessary parentheses +4x+4-3+*(+2x+6+)=-11 Reorder the terms in parentheses +4x+4+(-6x-18)=-11 Remove unnecessary parentheses +4x+4-6x-18=-11 move all terms containing x to the left and all other terms to the right. +4x-6x=-11-4+18 simplify left and right side of the equation. -2x=+3 divide both sides of the equation by -2 to get x. x=-1.5

Add answer